Is the Hypothesis of the Condensation-Induced Atmospheric Dynamics a New Theory of the Origin of the Winds? (2017)
Makarieva and Gorshkov (2007) proposed a new scientific hypothesis where a "previously unstudied property" associated with condensation is fundamental to a full understanding of atmospheric dynamics, and that appears in a confrontation with the standard theory, where the buoyancy force is the dominant driver of atmospheric motions. In this hypothesis condensation of water vapor in the Earth’s gravitational field is the driver of low-level air circulation, explaining phenomena like cyclones, monsoon circulations, and even the Hadley circulation. This hypothesis immediately attracted the attention of the academic community, especially of the hydrologists interested in a better understanding of the interaction between the hydrological cycle and the atmospheric circulation. This hypothesis also has received much criticism mainly from the meteorological expert community, which criticizes the validity of this hypothesis and the existence of this ``unstudied property.'' Although this proposed mechanism is controversial, we could not find any paper nor discussion that clearly shows that this hypothesis is physically wrong. In this thesis, we demonstrate that the proposed force is not new but is not effective because its contribution is canceled out in the buoyancy force. Therefore, this force does not play any role in the atmospheric circulation. We show that the description associated with this force is affected by serious problems in its physical formulation including violation of Newton's third law. We also reiterate that the role of the water cycle in the standard theory is essential to explain major atmospheric circulations, but without physical inconsistencies.